Long-term Development and Current Socio-Spatial Differentiation of Housing Estates in Prague, Czechia. - Ourednícek, Martin; Spacková, Petra; Pospísilová, Lucie (Springer Open, 2018)
The housing estate is perceived to be one of the main symbols of the socialist regime in the former Eastern Bloc. Immediately after the Velvet Revolution, housing estates were to some extent rejected by the general public as well as neglected in spatial planning and policies. At the same time, Prague s housing estates contained more than 40% of the city s population, thus representing the most important part of the built environment within the city. The main aims of the chapter are to evaluate the specific development of Prague s housing estates in the second half of the twentieth century, and then to explore the finer details of their inherent socio-spatial differentiation. The role of state and local housing policy is evaluated as the crucial factor in the current and future development of housing estates. The results are similar to those for many other CEE cities, and confirm that the transformation period had little impact on social structures within these residential areas and that the social mix sustains the main attribute of Prague s housing estates. New housing construction and ethnic differentiation are the most important processes to have changed the social environment of housing estates in Prague during the post-transformation period.
Keywords: Wohnungswesen; Wohnsiedlung; Wohnungspolitik; Sozialräumliche Gliederung; Sozialraum; Soziale Differenzierung; Stadtteilentwicklung; Fallbeispiel